USING COMPUTER TOOLS IN THE PROCESS OF SELF-EDUCATION OF FUTURE TEACHERS (Journal of Information Technologies in Education (ITE), 2010)
An attempt to ground the necessity of the optimum use of telecommunication resources in the process of self-education of students as a pedagogical condition of improvement of quality of preparation of future teachers to professional activity is carried out in the article. Technology of «Portfolіo», in which computer facilities of teaching of students will be realized most effectively, is grounded in particular.
Keywords: computer equipment; quality training of future teachers; self-education